1989
DOI: 10.1148/radiology.170.1.2909120
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced uterine changes: MR imaging.

Abstract: To assess the capability of magnetic resonance (MR) imaging to demonstrate postirradiation changes in the uterus, MR studies of 23 patients who had undergone radiation therapy were retrospectively examined and compared with those of 30 patients who had not undergone radiation therapy. MR findings were correlated with posthysterectomy histologic findings. In premenopausal women, radiation therapy induced (a) a decrease in uterine size demonstrable as early as 3 months after therapy ended; (b) a decrease in sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 0 publications
1
29
0
4
Order By: Relevance
“…None of the four women concerned conceived, despite having regular cycles over an extended period. One explanation for the lack of conception might be damage to the myometrium, with impaired function in the musculature and atrophic endometrium and impaired vasculature (39,40). Although the data are limited, it may be suggested that women who wish to have children but who have been exposed to radiation are less likely to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…None of the four women concerned conceived, despite having regular cycles over an extended period. One explanation for the lack of conception might be damage to the myometrium, with impaired function in the musculature and atrophic endometrium and impaired vasculature (39,40). Although the data are limited, it may be suggested that women who wish to have children but who have been exposed to radiation are less likely to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of the acute uterine effects of pelvic RT by DCE MRI, post-RT changes in cervical length, junctional zone anatomy and endometrial thickness were identified. Although the pathophysiology underlying these radiographic findings is not certain, it may be hypothesised that cervical shortening and junctional zone changes reflect atrophy or early fibrosis [14]. The reduction in endometrial thickness must be interpreted with caution, because it changes significantly with normal hormonal variation, and MRI evaluations were not performed at a specific phase of the menstrual cycle; however, bearing this limitation in mind, the finding may also be a sign of atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the only study on this topic was published in 1989 by Arrivé et al [14]. The authors compared the MRI studies of 23 patients who had undergone pelvic RT with 30 age-matched controls, and they correlated MR characteristics with posthysterectomy histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Ces effets pourraient cependant être liés à une carence estrogénique liée à une dysfonction ovarienne secondaire à l'irradiation. Arrive et al ont suivi les changements radiologiques de l'utérus de femmes traitées par radiothérapie pelvienne à la dose de 40-65 Gy [31]. À l'IRM, ils ont observé l'apparition d'un hyposignal en séquences T2 dans le myomètre, suivi d'une diminution de taille de l'utérus à 3 mois, puis de l'épaisseur du myomètre 5 mois après la radiothérapie.…”
Section: Dysfonction Utérineunclassified